Transcriptomic and Phenotypic Analyses Suggest a Network between the Transcriptional Regulators HrcA and σ(B) in Listeria monocytogenes - Hu, Yuewei (American Society for Microbiology (ASM), 2007)
Listeria monocytogenes HrcA and CtsR negatively regulate class I and III stress response genes, respectively, while σ(B) positively regulates the transcription of class II stress response genes. To define the HrcA regulon and identify interactions between HrcA, CtsR, and σ(B), we characterized newly generated L. monocytogenes ΔhrcA, ΔctsR ΔhrcA, and ΔhrcA ΔsigB strains, along with previously described ΔsigB, ΔctsR, and ΔctsR ΔsigB strains, using phenotypic assays (i.e., heat resistance, acid resistance, and invasion of human intestinal epithelial cells) and performed whole-genome transcriptome analysis of the ΔhrcA strain. The hrcA and sigB deletions had significant effects on heat resistance. While the hrcA deletion had no significant effect on acid resistance or invasion efficiency in Caco-2 cells, a linear regression model revealed a significant (P = 0.0493) effect of interactions between the hrcA deletion and the ctsR deletion on invasiveness. Microarray-based transcriptome analyses and promoter searches identified (i) 25 HrcA-repressed genes, including two operons (the groESL and dnaK operons, both confirmed as HrcA regulated by quantitative real-time PCR) and one gene directly repressed by HrcA, and (ii) 36 genes that showed lower transcript levels in the ΔhrcA strain and thus appear to be indirectly upregulated by HrcA. A number of genes were found to be coregulated by either HrcA and CtsR (2 genes), HrcA and σ(B) (31 genes), or all three regulators (5 genes, e.g., gadCB). Combined with previous evidence that σ(B) appears to directly regulate hrcA transcription, our data suggest that HrcA and σ(B), as well as CtsR, form a regulatory network that contributes to the transcription of a number of L. monocytogenes genes.